Cases from the Undiagnosed Diseases Network: The continued value of counseling skills in a new genomic era. Issue 2 (24th January 2019) - Macnamara, Ellen F.; Schoch, Kelly; Kelley, Emily G.; Fieg, Elizabeth; Brokamp, Elly; ,; Signer, Rebecca; LeBlanc, Kimberly; McConkie‐Rosell, Allyn; Palmer, Christina G.S.
Abstract: The "diagnostic odyssey" is well known and described in genetic counseling literature. Studies addressing the psychological, emotional, and financial costs of not having a diagnosis have shown how it permeates the lives of patients and families. The Undiagnosed Diseases Network aims to end this odyssey by providing diagnoses to individuals with undiagnosed conditions through multidisciplinary evaluations, whole exome and genome sequencing, and basic science research. It also provides an opportunity to learn from patients and families and to better understand their journeys and the impact of receiving a diagnosis. Seven cases are presented that outline challenges that come from working with chronically undiagnosed and newly diagnosed patients in a time when sequencing for clinical diagnosis is rapidly increasing. They illuminate the emotional journey of patients and families searching for a diagnosis and the mental health problems, financial distress, and chaos that can accompany not having answers. They also illustrate the surprising reactions patients and families can have to receiving a diagnosis, including anger, grief, and disappointment. While the lessons learned from these families are not novel, new strategies are presented for handling these challenges in undiagnosed and ultra‐rare populations, groups that will increase with the rise of clinical sequencing.